Essential oil composition of two Origanum L. taxa from Bingol (Turkey) - Özdemir, Fethi Ahmet; Kiliç, Ömer (Progress in Nutrition, 2017)
In this study aerial parts of the essential oils of Origanum acutidens L. and Origanum vulgare L. subsp. gracile (K. Koch) Ietswaart taxa were analyzed by HS-SPME/GC-MS. As a result forty one and thirty seven components were identified representing 89.7% and 90.4% of the oil, respectively. Carvacrol (37.5%), thymol (22.7%) and p-cymene (7.6%) were detected as main compounds of O. acutidens; carvacrol (30.8%), thymol (26.8%) and γ-terpinene (12.1%) were detected as the major constituents of O. vulgare subsp. gracile. With this study, chemotypes of studied taxa were identified as carvacrol and thymol. Additionly,  the studied plant samples were found to be rich in essential oils. The results are discussed in respect to natural products, renewable resources and chemotaxonomy.